2014
DOI: 10.4085/1062-6050-49.3.54
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Individuals With Chronic Ankle Instability

Abstract: Context: Individuals with chronic ankle instability (CAI) have reported decreased global and regional function. Despite the identification of functional deficits in those with CAI, more research is required to determine the extent to which CAI influences the multidimensional profile of health-related quality of life.Objective: To determine whether global, regional, and psychological health-related outcomes differ between individuals with and without CAI.Design: Case-control study. Setting: Laboratory.Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 36 publications
1
105
1
3
Order By: Relevance
“…In a systematic review, this group concluded that patients with CAI demonstrated disability and deficits in function on ankle-specific patient-reported outcome measures, as well as generic health-related QOL outcome measures compared with non-injured and LAS coper populations 193. In their own case–control study, this group reported that individuals with CAI displayed decreased function using the Disablement in the Physically Active Scale, while simultaneously displaying increased levels of fear of injury using the Fear-Avoidance Beliefs Questionnaire and the Tampa Scale of Kinesiophobia 190. Additionally, this group has demonstrated that the ankle-specific disability measures can be explained with physical and functional clinical measures, such as balance, strength or ROM 192.…”
Section: Section B: Mid-term and Long-term Consequences Of Lassmentioning
confidence: 96%
See 2 more Smart Citations
“…In a systematic review, this group concluded that patients with CAI demonstrated disability and deficits in function on ankle-specific patient-reported outcome measures, as well as generic health-related QOL outcome measures compared with non-injured and LAS coper populations 193. In their own case–control study, this group reported that individuals with CAI displayed decreased function using the Disablement in the Physically Active Scale, while simultaneously displaying increased levels of fear of injury using the Fear-Avoidance Beliefs Questionnaire and the Tampa Scale of Kinesiophobia 190. Additionally, this group has demonstrated that the ankle-specific disability measures can be explained with physical and functional clinical measures, such as balance, strength or ROM 192.…”
Section: Section B: Mid-term and Long-term Consequences Of Lassmentioning
confidence: 96%
“…Houston et al 190 192 193 also have considered the effect of ankle injury history on QOL, and what factors might help explain this decline. In a systematic review, this group concluded that patients with CAI demonstrated disability and deficits in function on ankle-specific patient-reported outcome measures, as well as generic health-related QOL outcome measures compared with non-injured and LAS coper populations 193.…”
Section: Section B: Mid-term and Long-term Consequences Of Lassmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower extremity injuries are responsible for up to 70% of the time lost from athletic participation, and knee and ankle sprains encompass a large percentage of the injuries . While lower extremity injuries typically have an immediate impact on function, they often lead to repetitive injury, recurrent instability, and decreased health‐related quality of life which can have long term negative implications . Therefore, lower extremity injuries are common, and understanding the contributing factors to residual problems following these injuries continues to be an important area of research.…”
mentioning
confidence: 99%
“…3 Lateral ankle sprain (LAS) is the most commonly reported injury resulting in 10 or more days of activity loss in collegiate women's soccer. 2 Along with time loss, there is added concern for recurrent injury, 4 impaired neuromuscular control, [5][6][7] decreased physical activity, 7,8 decreased health-related quality of life, 8 and posttraumatic osteoarthritis 9 in individuals with a history of LAS.…”
Section: Introductionmentioning
confidence: 99%